Measurement of efficiency and effectiveness of PPR in terms of time and cost overruns for roads and highways department and identification of important factors for time and cost overruns - Yousuf, Mohammed (BRAC University, 2014)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2012.